2018
DOI: 10.1063/1674-0068/31/cjcp1712238
|View full text |Cite
|
Sign up to set email alerts
|

Order-Disorder transition of carboxyl terminated chains in polydiacetylenes vesicles probed by second harmonic generation and two-photon fluorescence

Abstract: To understand and control the interfacial properties of polydiacetylenes (PDAs) vesicles with π-conjugated backbone is very important for their colorimetric sensing of chemical and biological targets. In this work, we adopted 10, 12-pentacosadiynoic acid (PCDA) as the model molecule to prepare PDAs vesicles in aqueous solution with different forms (from monomer to blue-to-purple-to-red phase) by controlling the UV irradiation dose. The variations of the interfacial conformation of PDAs vesicles during chromati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Based on the principles of the second-order nonlinear phenomenon, the D289 molecules oriented on the surface of lipid membranes may contribute to enhanced SHG emission because of the broken inversion symmetry . It was also shown that the D289 molecules on the lipid surface contributed to enhanced TPF emission, , possibly because of the well-known aggregation-induced emission (AIE) mechanism or the enhancement of the fluorescence efficiency of D289 with its distribution in the lipid membrane in K562 cells. A similar enhancement in the TPF efficiency from an anticancer drug, doxorubicin, during its interaction with lipid bilayer was recently reported …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the principles of the second-order nonlinear phenomenon, the D289 molecules oriented on the surface of lipid membranes may contribute to enhanced SHG emission because of the broken inversion symmetry . It was also shown that the D289 molecules on the lipid surface contributed to enhanced TPF emission, , possibly because of the well-known aggregation-induced emission (AIE) mechanism or the enhancement of the fluorescence efficiency of D289 with its distribution in the lipid membrane in K562 cells. A similar enhancement in the TPF efficiency from an anticancer drug, doxorubicin, during its interaction with lipid bilayer was recently reported …”
Section: Resultsmentioning
confidence: 99%
“…7,10,33,37,40,41 Recently, we have demonstrated that the dynamics of dye or drug molecules on the lipid surface may be investigated not only by the interface selective SHG method but also by the twophoton fluorescence (TPF) method, which is also sensitive to the dye or drug molecules on the surface of lipid bilayers because their fluorescence efficiency was notably altered (quenched or enhanced) with the changed chemical environment. 11,37,38,42 In this work, we used SHG and TPF methods to investigate the adsorption and cross-membrane transport of D289 on K562 cells and the subcellular organelles in them. It was revealed that D289 adsorbed on the K562 surface may transport in the cell at a relatively slow rate (∼1000s).…”
mentioning
confidence: 99%
“…Second harmonic generation (SHG) has been demonstrated as a powerful technique in the analysis of molecular density and orientation at interfaces, benefiting from its interface selectively and submonolayer sensitivity. On the basis of this advantage, SHG has been used to study molecular transportation through liposome membranes and living cell membranes in situ and in real time. For example, Prof. Eisenthal’s group was first to detect the transportation of dye molecules across the bilayer of a phospholipid liposome with the help of the SHG technique . The influence of cholesterol on the delivery rate of an organic cation across the dioleoylphosphatidylglycerol liposome surface has also been analyzed .…”
Section: Introductionmentioning
confidence: 99%
“…Being the opposite to the ACQ effect observed for the aforementioned anthracyclines, some molecules were revealed to emit enhanced TPF signal upon their aggregating and embedding on/in the lipid bilayers [62,75,76]. This property is also helpful in analyzing its interfacial behaviors on lipids.…”
Section: Investigating the Vesicle Formation Process And Dynamics Of ...mentioning
confidence: 93%